Psychosocial Determinants of Substance Use among Physically Challenged Individuals in Ibadan - Akinniyi , Rotimi Jacob; Ishola, Ajibola Abdulrahamon; Oyeleke , Johnson T.; Akinniyi , Boluwatife Joseph; Adekunle , Pbebian Funmilayo (Universitas Pendidikan Ganesha, 2024)
Substance use among physically challenged individuals poses various risks to their health and well-being, as well as to the broader community. Excessive alcohol and drug consumption can exacerbate existing health conditions and impair physical and cognitive functioning, leading to increased vulnerability to accidents, injuries, and other adverse outcomes. Therefore the aim of this study is to investigate the psychosocial determinants impacting alcohol and drug use within the physically challenged community in Ibadan. Employing a cross-sectional data collection uncovers the intricate relationship between social, psychological, and environmental factors and substance use behaviors. Results highlight the profound influence of social isolation, stigma, and limited access to support services on substance use patterns among the physically challenged in Ibadan. The findings underscore the urgency for tailored interventions and enhanced support services aimed at addressing the unique needs of this population. This study contributes valuable insights for policymakers, healthcare providers, and community organizations working to improve the quality of life for physically challenged individuals in Ibadan and similar contexts.